2021
DOI: 10.3947/ic.2021.0051
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiologic Efficacy and Safety of Imipenem/Cilastatin/Relebactam in Complicated Infections: A Meta-analysis

Abstract: Background Antimicrobial resistance is on the rise. The use of redundant and inappropriate antibiotics is contributing to recurrent infections and resistance. Newer antibiotics with more robust coverage for Gram-negative bacteria are in great demand for complicated urinary tract infections (cUTIs), complicated intra-abdominal infections (cIAIs), hospital-acquired bacterial pneumonia (HABP), and ventilator-associated bacterial pneumonia (VABP). Materials and Methods We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The ratio of ICU and general ward use between death vs cured is based on the hospital resource utilization analysis from the ASPECT-NP trial [41], which is limited to only ventilated HABP/VABP patients resource costs, and AE management cost. For the drug treatment cost, the wholesale acquisition costs for IMI/REL ($6688/25 vials 500 mg/ 250 mg units), CMS ($336/12 vials 150 mg), and IMI ($816/25 vials, 500 mg/500 mg) were sourced from the 2020 RED BOOK online database [13] and combined with trial-observed treatment durations to compute total acquisition costs [18]. Drug administration costs were not included in the model base case, as it is assumed these costs are implicitly captured by resource use (hospitalization) costs.…”
Section: Utility Inputs Hospitalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of ICU and general ward use between death vs cured is based on the hospital resource utilization analysis from the ASPECT-NP trial [41], which is limited to only ventilated HABP/VABP patients resource costs, and AE management cost. For the drug treatment cost, the wholesale acquisition costs for IMI/REL ($6688/25 vials 500 mg/ 250 mg units), CMS ($336/12 vials 150 mg), and IMI ($816/25 vials, 500 mg/500 mg) were sourced from the 2020 RED BOOK online database [13] and combined with trial-observed treatment durations to compute total acquisition costs [18]. Drug administration costs were not included in the model base case, as it is assumed these costs are implicitly captured by resource use (hospitalization) costs.…”
Section: Utility Inputs Hospitalizationmentioning
confidence: 99%
“…Imipenem/cilastatin/relebactam (IMI/REL), a combination of a b-lactam antibiotic (imipenem/cilastatin) and a novel b-lactamase inhibitor (relebactam), provides a treatment alternative with a favorable efficacy and tolerability profile for patients with CNS GNIs [13]. The novel b-lactamase inhibitor (relebactam) restores the activity of imipenem against imipenem-resistant isolates such as KPC-producing Enterobacterales and/or against Pseudomonas aeruginosa isolates showing CNS due to porin loss in combination with AmpC expression [13].…”
Section: Introductionmentioning
confidence: 99%
“…IMI/REL is a new antibiotic combination, bactericidal by its binding inhibition to penicillin binding proteins (PBP1 and PBP2). Recently, it has been approved by the FDA for use in ventilator-associated pneumonia (VAP) and hospital-acquired pneumonia (HAP) in June 2020 [1][2][3]. tration and active tubular secretion.…”
Section: Introductionmentioning
confidence: 99%
“…I read with great interest a recently published meta-analysis of Sahara et al [ 1 ] entitled “Clinical and microbiologic efficacy and safety of imipenem/cilastatin/relebactam in complicated infections: a meta-analysis.” According to the article, the systematic search was performed by related keywords in international databases; Cochrane Central Registry of Clinical Trials, Embase, and PubMed. After selection based on inclusion and exclusion criteria, four randomized controlled trials articles were included in this meta-analysis.…”
mentioning
confidence: 99%